Technology and religion: Islam, Christianity and materialism - Schuurman, E. (Koers, 2011)
The Western world and the world of Islam share a history, but they also differ greatly. The rise of terrorism has once again made us fully aware of that. In these tense times I would like to consider a question that is rarely raised today, yet which may be very relevant and very revealing: What attitude do these two worlds take toward technology?